Sister outsider - Lorde, Audre (Penguin Books, 2020)
"At once a searing indictment of a racist, patriarchal society and a manual for claiming an intersectional identity, Sister Outsider is a comprehensive collection of the lauded poet and writer Audre Lorde's most famous and influential works of nonfiction prose. Sister Outsider depicts the idea of "difference"--whether through race, gender, or sexuality--as a powerful tool for empowerment that can be used as a catalyst for change. Throughout the fifteen essays and speeches that comprise the volume, Lorde asserts that because she is a black, queer woman, she is considered an outsider, but that it is precisely her outsider perspective that allows her to see the various layers of identity-based oppression. A pioneer of intersectional feminism, Sister Outsider encourages the reader to embrace their difference and weaponize it for change, a once-radical 20th-century idea that has become a full-blown movement today. Penguin Classics launches a new hardcover series with five American classics that are relevant and timeless in their power, and part of a dynamic and diverse landscape of classic fiction and nonfiction from almost seventy-five years of classics publishing. Penguin Vitae provides readers with beautifully designed classics that have shaped the course of their lives, and welcomes new readers to discover these literary gifts of personal inspiration, intellectual engagement, and creative originality"--